Dampak Penggunaan Gadget Terhadap Hafalan Qur’an Santri - Juandi Pasaribu; Nurfarida; Juliana Batubara (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Researchers realize that today's increasing use of electronics from the rise of technology limits our ability to remember things. Later than that, considering the assumption that gadget devices could trigger a tendency to use applications, the authors were encouraged to go into further details about it. This is due to the fact that recording the Quran on a gadget may take a lot of time and focus and can even reduce the amount of time it takes to remember it. The research method used by the author is field research, field research with a survey approach. The author uses phenomenological approaches in qualitative descriptive methods. Since not all population centres were used as samples, structured interviews with these samples were collected for this research using unsaturated sampling. Research findings show that the influence of gagdet on the centers of memorizing the Qur’an in the Educational Park of Al-Qur’an (TPQ) Mosque Muhajirin Cold Water at Koto Tangah, Padang Baik positive and negative effects can be experienced by the reader of the Quran because of the gadget. Positive effects for the TPQ Mosque muhajirin cold water at Kato Tangah include improved access to knowledge, new perspectives, help with academic tasks, ease of communication, and the ability to promote creativity within the center. The Muhajrin mosque may have had negative effects such as lost time, missed opportunity to participate in other events, the termination of the Tahfizh program, and the abolition of rituals.